The analysis of employee performance: The effect of social insurance, work environment, and incentives - Tassya Dzulfiana Salsabella; Tania Chusna Azzahra (Universitas Ahmad Dahlan, 2025)
Purpose-Post offices are facilities that provide services for receiving, collecting, sorting, transmitting, and delivering letters and packages. The phenomenon shows that there is a discrepancy between theory and reality. This study aims to analyze the influence of social insurance, work environment, and incentives on employee performance. Methodology-This study uses a quantitative approach by conducting a survey using a questionnaire. The respondents of this study are employees working at the Yogyakarta Central Post Office, Indonesia. The research data was obtained from 50 respondents using a saturated sampling technique. Data analysis was carried out through validity tests, reliability tests, and hypothesis testing using SPSS version 25 statistical tools. Findings-The results of the study indicate that incentives have a positive effect on employee performance behavior. However, social insurance and the work environment in this study were found to have no positive effect on employee performance. This means that social insurance and the work environment cannot automatically be considered determining factors for employee performance, as there are other stronger factors influencing performance, such as incentives. Research Limitations- The scope of this study focuses on employees working at the Yogyakarta Central Post Office, Indonesia. Therefore, the results of this study do not represent employees working at branch post offices or other regions. In addition, the number of respondents is still relatively small, so it is recommended that future studies increase the number of research samples or expand the scope of the sample. Novelty-This study provides a deeper understanding of the relationship between employee performance and the factors that influence it. These findings are expected to provide practical recommendations for policymakers and practitioners to improve employee performance